Papp, Alfred & Schmíd, Manfred E., 1985. DIE FOSSILENFORAMINIFEREDESTERnAREN BECKENsVONWIEN, REVlSION DER MONOGRAPHIE VON ALClDE D'ORBIGNY(1846). Abhandl. Geol. Bundesanstalt, Rasumofskygasse 23, Postfach 154, Wíen, A-1031, Austria. (Ameghiniana, 2013)
no presenta